As Little Regard in Life as in Death: A Critical Analysis of Subjugation and Accountability Following Deaths in Psychiatric Detention. (January 2017) - Speed, Carly
This article draws on insights from doctoral research into deaths in psychiatric detention in England and Wales. As the article demonstrates, the response to patients in death has often been reflective of the response to them in life, both historically and contemporarily. Furthermore, the families and friends of patients and those who raised concerns have also been treated in a similar manner to patients themselves. Some of the key areas explored in the article are the exercise of power over patients and their advocates by the medical profession and other official bodies, including the oppression, categorization, and dismissal that they have faced. The contestations and challenges of this power will also be explored and how dominant voices have been challenged through the emergence of alternative truths . Post-death procedures will also be critically examined, primarily the inquest and investigation processes, with a focus on issues surrounding the secrecy and lack of accountability apparent.